Selecting relationship and uploads: mediatisation studies on Indonesian migrant worker’s media engagement - Yudha, Reza Praditya (Jurnal Studi Komunikasi, 2021)
Indonesian migrant workers use social media for various needs. Workers’ engagement on social media is usually related to their hometown and socio-culture abroad. This study draws on Couldry and Hepp’s idea of ​​mediatisation to examine the interrelation of communication practices and media use to socio-cultural dynamics. The author argues that media engagement is related to socio-cultural context, especially workers’ socio-cultural group. Applying virtual ethnography, the author analysed media types, actor constellations, communication themes, and practices. The findings show that workers select relationships, posts, and types of social media, and their social media engagement is strongly related to their hometown socio-culture. Workers use Facebook to present hardworking, collectively, and homely self-images, WhatsApp to connect to intimate relationships or close family, while young workers choose, and Instagram to construct a modern, successful, and expressive self-image. Additionally, workers join local group accounts to update news and maintain a sense of belonging to the hometown.